The course of the judo fight at the 2011 World Championship - Stankovic, N.; Cuk, S.; Milosevic, N.; Stamenkovic, S. (Facta Universitatis: Series Physical Education and Sport, 2015)
The aim of the study was to investigate the course of the judo fight in different weight categories at the 2011 Senior World Championship held in Paris. The sample consisted of 140 fights in the men's competition from the World Championship held in 2011 in Paris. From each of the seven weight categories, twenty of the most important matches were analyzed. The categories included light (-60kg and -66kg), middle (-73kg, -81kg and -90kg) and heavy (-100kg and +100kg). A total of 959 situations were observed. The following variables were analyzed: actions, group of the applied nage waza and kumikata stance. There were statistical differences (p=0.05) between the different weight categories in all the analyzed parameters. The results have shown that judokas need to conduct a great number of attack attempts in order to score (65.38% of all the actions were unsuccessful throw attempts). They preferred te waza (35.87%) and ashi waza (34.82) techniques from the kenka yotsu (37.94%) and ai yotsu (24.11%) gripping stance. As coaching advice, the number of training situations that favor attacking from thekenka and ai yotsu stance and defending from ashi and te waza attacks should be increased.